2010
DOI: 10.1002/da.20655
|View full text |Cite
|
Sign up to set email alerts
|

Specific phobia: a review of DSM-IV specific phobia and preliminary recommendations for DSM-V

Abstract: The present review was conducted in order to evaluate the current diagnostic criteria for specific phobia (SP) in light of the empirical evidence gathered since DSM-IV and to propose changes to DSM-V where change is clearly and reliably indicated by the evidence. In response to questions put forth by the DSM-V Anxiety, OC Spectrum, Posttraumatic, and Dissociative Disorder Work Group, four primary areas were determined for this review: the accuracy and utility of the current SP type classification system, the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
122
5
12

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(160 citation statements)
references
References 98 publications
13
122
5
12
Order By: Relevance
“…A higher female susceptibility has also been reported for the specific phobia fear of heights [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The prepubertal children in the current study showed no gender predominance in susceptibility.…”
Section: Gender-specific Differences?supporting
confidence: 68%
See 2 more Smart Citations
“…A higher female susceptibility has also been reported for the specific phobia fear of heights [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The prepubertal children in the current study showed no gender predominance in susceptibility.…”
Section: Gender-specific Differences?supporting
confidence: 68%
“…The life-time prevalence of the specific phobia fear of heights (acrophobia) ranged between 3.1 and 6.4% [2][3][4]. If the survey on fear of heights includes the less severe form of visual height intolerance as described in the Introduction, the prevalence rate in adults is much higher, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With life-time prevalence rates of over 10% (Kessler, Berglund, Demler, Jin, Merikangas, & Walters, 2005a;LeBeau, Glenn, Liao, Wittchen, Beesdo-Baum, Ollendick, & Craske, 2010), specific phobias are the most prevalent group of mental disorders. A specific phobia is a common, long lasting, often chronic anxiety disorder (Depla et al, 2008;Goisman, Allsworth, Rogers, Warshaw, Goldenberg, Vasile, Rodriguez-Villa, Mallya, & Keller, 1998), associated with serious impairment (Magee, Eaton, Wittchen, McGonagle, & Kessler, 1996;Alonso et al, 2004;Oosterink, de Jongh & Hoogstraten, 2009) that represents a serious public health problem with a substantial economic burden (Alonso et al, 2004;Greenberg, Sisitsky, Kessler, Finkelstein, Berndt, Davidson, Ballenger, & Fyer, 1999;Robins, Helzer, Weismann, Orvaschel, Gruenberg, Burke, & Regier, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Such information may particularly be important since some phobic conditions differ in their response to a confrontation with a phobic stimulus. For example, blood-injury-injection phobia appears to be uniquely associated with fainting in phobic situations, and has been found to be especially responsive to an intervention that is tailored to its physiological profile (i.e., applied tension; LeBeau, Glenn, Liao, Wittchen, Beesdo-Baum, Ollendick & Craske, 2010). Although fears are by definition lower in clinical severity than phobias, highly fearful individuals meet at least some criteria for specific phobia and therefore they may still be in need of straightforward and effective, exposure-based, interventions to alleviate the severity of their distress and avoidance patterns.…”
Section: Introductionmentioning
confidence: 99%